Audit Sistem Informasi Aplikasi Absensi Pada Inl International Technology Menggunakan Framework Cobit 5 - Muchlis Imam Santoso; Eva Zuraidah (STMIK Budi Darma, 2023)
An information system audit is carried out to ensure that the system procedures in the institution function properly, using the Cobit 5 framework in auditing the attendance system at INL International Tehnology Pte. Ltd., because there is no standard operating attendance system, there are still deficiencies where in the application to use it in an orderly and correct manner, if we are late for absence there is no warning that we are late for absence from work. The results obtained are the sequence of domains with the highest value, namely the EDM01 domain maturity level value of 3.64 Fully Achieved achievement value, gets the Established Process level in IT capability, and a gap value of 0.64 from the target level 3. MEA01 maturity level value of 3.18 Fully Achieved achievement value, gets the Established Process level in IT capability, and the value gap of 0.18 from the target level 3. BAI08 maturity level value of 2.93 Fully Achieved achievement value, got the Managed Process level in IT capabilities, and a gap value of 0.07 from the target level 3. DSS02 maturity level value of 1.59 Fully achievement value Achieved, got the Performed Process level in IT capabilities, and the gap value is -1.41 from the target level 3. and APO11 mend get a maturity level value of 0.95, the Fully Achieved achievement score, get the Incomplete Process level in IT capabilities, and a gap value of -2.05 from target levels 3 and 2 and the highest score domain order questionnaire, namely domain EDM01, maturity level value 3.64, gap value 0, 64. MEA01 maturity level value is 3.18, gap value is 0.18. BAI08 has a maturity level of 2.93 with a gap value of 0.07. DSS02 maturity level value is 1.59, gap value is -1.41. and APO11 maturity level value of 0.95 gap value of -2.05